Semantic and Grammar Categories in Norm and Pathology - Glozman, Janna (East European Journal of Psycholinguistics, 2015)
Categorization is one of the most important human abilities for cognition and reasoning. The categorization process follows a long ontogenetic development with appropriation of both verbal notions and human experience. Abstract notions, including grammar categories appear at the final period of this development. A delayed development of semantic categories is described in special psychology and medicine as mental retardation (olygophrenia) or slow intellectual development. The types and mechanisms of underdevelopment or disturbances of grammar categories are not very clear in spite of their significance for understanding the aphasia, alalia and dysgraphia. The paper analyzes such kinds of grammar categorization disturbances as troubles of words paradigmatic realizing, secondary etymologization and transformations of vocabulary internal structure after cortical and subcortical brain damages as well as in speech development. New experimental methods of study the grammar notions and grammar – semantic relationship are described. The disturbances of grammar notions are explained through an underdevelopment or damages of the metalinguistic function providing a feed-back, the control of own communication and ability to adjust it to communicative expectancies of the others. This function is known as the “linguistic feeling”. We analyze different understanding of this phenomenon, steps of its formation in preschoolers and schoolchildren and its specific disturbances in mentally retarded children with semantic categories lack. References Bobryk, J. (2000). Modern and postmodern visions of the mind. Polish Psychological Bulletin, 31, 2, 93 – 100. Bozhovich, E. (2000) Etapy razvitiya yazykovoy kompetentsii rebenka [Steps in development of linguistic competence in child]. In: Linguistic conscience: content and meaning (p. 34). Moscow: Linguistics Institute Press. Bozhovich, L.I. (1946). Znacheniye osoznaniya yazykovyh kategoriy v obuchenii pravopisaniyu [Importance of linguistic categories realizing in writing learning]. Izvestiya of Russian Pedagogical Academy, 3. Danilova, N.N., Strabykina, E.A., Glozman, J.M., Pligina, A.M. (2015) O mekhanizme kategorizatsii i yego narusheniyah pri parkinsonizme [On categorization mechanism and its troubles in Parkinsonism] In: Proceedings of the VI Congress of Russian Psychological Association. Moscow. In Press. Galperin, P. (1959). Razvitiye issledovaniy po formirovaniyu umstvennyh deystviy [Progress in studies of mental actions formations]. Psychological Science in the USSR, 1 (pp. 441–469). Moscow: Russian Pedagogical Academy Press. Glozman, J. (1975). K voprosu o structure expressivnogo agrammatizma pri raznih formah afazii [On the structure of expressive agrammatism in different kinds of aphasia]. In: Problems of aphasia and reeducation (pp. 101–115). Moscow: Moscow Univ. Press. Glozman, J. (1996). Issledovaniye struktury lexicona pri korkovyh i podkorkovyh porazheniyah mozga [A study of vocabulary structure after cortical and subcortical brain damages]. Vestnik Moscovskogo Universiteta, 2, 67–72. Glozman, J. (2004). Communication Disorders and Personality. New York: Kluwer Academic/ Plenum Publishers. Kalita, N. (1976). O prirode i makhanizmakh narusheniya nominativnoy funktsii rechi pri akustiko-mnesticheskoy afazii [On nature and mechanisms of naming troubles in acoustic-mnestic aphasia]. Ph.D. dissertation. Moscow: Moscow State University. Lalaeva, R. (1993). O chuvstve yazyka u umstvenno otstalyh shkolnikov [On the sense of language in mentally retarded children]. In: Speech trouble. Methods of assessment and remediation, (pp. 115–122). St. Petersburg: Meditsina. Luria, A. (2004). Lektsii po Obshey Psykhologii [Lectures in General Psychology]. Moscow: Piter. Pevzner, M. (1959). Deti – Oligophreny [Children with Oligophrenia]. Moscow: Pedagogica. Psykhologichesky Slovar’ [Psychological Dictionary] (1996). V. Zinchenko, B. Mescheryakov (Eds). Moscow: Pedagogika-Press. Tseytlin, S. (2000) Yazyk i Rebenok. Linguistika Detskoy Rechi. [Language and Child. Linguistics of children speech]. Moscow: Vlados. Saharny, L. (1978) Proizvodnoye slovo kak component kommunikativnoy nominatsii [A derivate word as a component of communicative nomination]. In: Psycholinguistic and sociolinguistic speech determination, (pp. 65–181). Moscow: Moscow Univ. Press. Vygotsky, L. (1956). Isbranniye Psykhologicheskiye Issledovaniya [Selected Psychological Papers]. Moscow: Pedagogika.